The Parisian Tailleur from 1911, a milestone in Women's Social Attire in Brazil - Maia Pereira, Perciliana (2025)
The general catalogue of the Au Palais Royal store from 1911-1912, established in São Paulo, to cater to the refined tastes of the Frenchified clientele of the coffee-producing São Paulo elite, introduced its customers to the Parisian Tailleur, a garment with a well-defined silhouette that shaped the image of women at the beginning of the 20th century, prior to the outbreak of World War I. The article proposes research and recreation of a garment within the framework of historical costume studies. The study follows, as its method, the system proposed by Italiano and Viana (2024), which begins with historiographical research, proceeds through the analysis of iconographic records, and includes searches in pattern-making and garment construction manuals from the same period to support the stages of historical recreation. As a result, the study is expected to contribute to expanding knowledge in the field, offering relevant material for students, costume designers, and other researchers and professionals in the clothing sector. It aims to serve as a reference for both contemporary and historical garment creation, intended for exhibitions or artistic productions. Other important sources include Bonadio (2007), Boucher (2010), and Butterick (1911).